Psychosocial Profile of Bullies, Victims, and Bully-Victims: A Cross-Sectional Study - Leiner, Marie; Dwivedi, Alok K.; Villanos, Maria Theresa M.; Singh, Namrata; Blunk, Dan I.; Peinado, Jesus (Frontiers in Pediatrics, 2014)
While adverse conditions in a child’s life do not excuse inappropriate behavior, they may cause emotional and behavioral problems that require treatment as a preventive measure to reduce the likelihood of bullying. We aimed to identify differences in the psychosocial profiles of adolescents who classified themselves as bullies, victims, or bully-victims. We performed a cross-sectional study in which data were collected between January 2009 and January 2010 from seven university-based clinics in a large metropolitan area with a predominantly Mexican-American population. We collected data on physical aggression among adolescents who self-categorized into the following groups: uninvolved, bullies, victims, and bully-victims. We determined the psychosocial profiles of the adolescents based on responses to the Youth Self Report (YSR) and parent’s responses to the Child Behavior Checklist (CBCL). A one-way analysis of variance and multivariate regression analyses were performed to compare the various components of the psychosocial profiles among the groups. Our analysis of the CBCL and the YSR assessments identified differences between the uninvolved group and one or more of the other groups. No significant differences were observed among the bully, victim, and bully-victim groups based on the CBCL. We did find significant differences among those groups based on the YSR, however. Our results suggest that emotional and behavioral problems exist among bullies, victims, and bully-victims. Therefore, treatment should not focus only on the victims of bullying; treatment is equally important for the other groups (bullies and bully-victims). Failure to adequately treat the underlying problems experienced by all three groups of individuals could allow the problems of bullying to continue.